Hubungan Iklim Sekolah dan Kepuasan Kerja dengan Kinerja Tenaga Administrasi Sekolah - Wahyu Adi Setiawan; Ibrahim Bafadal; Wildan Zulkarnain; Wahyu Adi Setiawan; Ibrahim Bafadal (Universitas Negeri Malang, 2022)
Abstract: This study aims to describe the level of school climate, the level of job satisfaction, the level of performance of school administration staff, the relationship of the school climate with the performance of school administration staff, the relationship of job satisfaction with the performance of school administration staff, and the relationship between school climate and job satisfaction with the school administration staff performance at public senior high school in Tulungagung. This study uses a quantitative approach to the type of descriptive-correlational quantitative research. The results showed that the level of the school climate in the category was quite conducive, the level of job satisfaction in the medium category, the level of performance in the medium category, the relationship between the school climate and the school administration staff performance at state senior high school in Tulungagung, the relationship between job satisfaction and the school administration staff performance at public senior high school in Tulungagung, and there is a relationship between the school climate and job satisfaction with the school administration staff performance at public senior high school in Tulungagung. The effective contribution of the school climate to performance is 1 percent and job satisfaction to performance is 16.8 percent, the rest is another variable of 83.2 percent in influencing performance. The relative contribution of the school climate to performance is 6 percent and job satisfaction to performance is 94 percent. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan tingkat iklim sekolah, tingkat kepuasan kerja, tingkat kinerja tenaga administrasi sekolah, hubungan iklim sekolah dengan kinerja tenaga administrasi sekolah, hubungan kepuasan kerja dengan kinerja tenaga administrasi sekolah, dan hubungan iklim sekolah dan kepuasan kerja dengan kinerja tenaga administrasi sekolah di SMAN se-Tulungagung. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian kuantitaif deskriptif-korelasional. Hasil penelitian menunjukkan bahwa tingkat iklim sekolah pada ketegori cukup kondusif, tingkat kepuasan kerja pada kategori sedang, tingkat kinerja pada kategori sedang, adanya hubungan iklim sekolah dengan kinerja tenaga administrasi sekolah di SMAN se-Tulungagung, adanya hubungan kepuasan kerja dengan kinerja tenaga administrasi sekolah di SMAN se-Tulungagung, dan ada hubungan iklim sekolah dan kepuasan kerja dengan kinerja tenaga administrasi sekolah di SMAN se-Tulungagung. Sumbangan efektif iklim sekolah terhadap kinerja sebesar 1 persen dan kepuasan kerja terhadap kinerja sebesar 16,8 persen, Sisanya yakni variabel lain sebesar 83,2 persen dalam memengaruhi kinerja. Sumbangan relatif iklim sekolah terhadap kinerja sebesar 6 persen dan kepuasan kerja terhadap kinerja sebesar 94 persen.